2010
DOI: 10.1038/nrrheum.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Novel functions for NFκB: inhibition of bone formation

Abstract: NFκB is a family of transcription factors involved in immunity and the normal functioning of many tissues. It has been well studied in osteoclasts, and new data indicate an important role for NFκB in the negative regulation of bone formation. In this article, we discuss how NFκB activation affects osteoblast function and bone formation. In particular, we describe how reduced NFκB activity in osteoblasts results in an increase in bone formation via enhanced c-Jun N-terminal kinase (JNK) activity, which regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 51 publications
(59 reference statements)
2
128
0
1
Order By: Relevance
“…We then determined the mechanism by which NF-B activation may induce osteoblast dysfunctions in ⌬F508-CFTR cells. Up to now, few NF-B target genes have been identified in osteoblasts (24). One potential NF-B target gene is Fra1, which is an essential regulator of bone formation (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then determined the mechanism by which NF-B activation may induce osteoblast dysfunctions in ⌬F508-CFTR cells. Up to now, few NF-B target genes have been identified in osteoblasts (24). One potential NF-B target gene is Fra1, which is an essential regulator of bone formation (46).…”
Section: Discussionmentioning
confidence: 99%
“…In bone, exacerbated NF-B signaling is known to cause inflammation (22) and to promote osteoclastogenesis (23). In addition, recent studies indicate that NF-B signaling negatively controls bone formation (23)(24)(25)(26). Mechanistically, NF-B activation in osteoblastic cells reduces expression of the key osteogenic transcription factor Runx2 (27) and increases expression of the E3 ubiquitin ligase Smurf1 (28), resulting in increased proteasomal degradation of RUNX2 (29 -32).…”
mentioning
confidence: 99%
“…Oxidative stress and chronic inflammation in pathological BM microenvironment greatly promote osteoclast differentiation and activity thus uncoupling bone resorption from formation by accelerating the former [58,59]. In such circumstances, the production of bone forming signaling molecules such as TGF-β1 and BMPs are reduced [60] whereas the production of their antagonists is increased [61].…”
Section: How Pathological Conditions Change the Bm?mentioning
confidence: 99%
“…Also, this result agrees, with Chang et al, (2009) who showed an increase in NF-κβ activity in ovariectomy and evidenced that estrogen regulates NF-κβ in osteoblasts in vivo. The activation of NF-κβ due to estrogen deficiency not only promotes osteoclast activation, osteoclast survival and bone resorption, but simultaneously inhibits osteoblast function (Krum et al, 2010). Historically, NF-κβ has not been considered as a key mediator of osteoblast signaling, but several studies have shown that NF-κβ inhibits both osteoblast differentiation and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Given that RANKL induces activation of several pathways shown to be necessary for osteoclastogenesis in vitro, it is quite intriguing that the constitutive activation of NF-κB is sufficient to mediate osteoclast differentiation (Novack, 2011). Binding of RANKL to the RANK receptor leads to subsequent NF-κβ-mediated induction of osteoclast differentiation genes, prolonged survival of osteoclast and increased bone resorption (Krum et al, 2010).…”
Section: Discussionmentioning
confidence: 99%